Electronic excitation produced by proton moving inside polystyrene using Drude model - Mezher, Sahar (University of Thi-Qar Journal of Science, 2019)
The electronic response of target is characterized by its energy-loss function (ELF) , which it described by several models that fit the available experimental data (at zero momentum transfer), but use different approaches to obtain the Bethe surface so that is to extend the (ELF) to include any energy and momentum transferred. In the present research the Drude dielectric formalism had been used to calculate the probability for an energetic proton to produce electronic excitations in target, Target material used in this research is a polymeric material which is polystyrene. And calculate the effects of ionization fraction of Partial Stopping Power Effective Charge (PSPEC) of polystyrene have been studied and taking into consideration the electronic excitation in the target. Drude Energy Loss Function DELF has been used to take in the consideration the charge exchange, screening length and charge density. FORTRAN-90 program forePolystyrenH . has been written for the mathematical equations using software Compaq visual Fortran90 V 6.6, for linking and execute.